PERAN MAHASISWA ILMU PERPUSTAKAAN UINSU PADA STRATEGI PENGOLAHAN BAHAN PUSTAKA DI PERPUSTAKAAN YP NUR ADIA - Muhammad Ridwan; Wahyu Purwaningtyas; Khirpal Fikri (Jurnal Ilmiah Widya Sosiopolitika, 2025)
The processing of library materials is a key activity that influences the quality of returned information; however, many school libraries face challenges such as limited professional staff and weak processing procedures. This study explores the role of Library Science students from UINSU in improving the processing of library materials at the Nur Adia School Library. The research used a qualitative method with a case study approach. The results show that students not only helped complete various technical tasks related to material processing but also provided significant conceptual contributions. Their interactions accelerated processing activities, especially classification, and supported the adoption of simple LMS-based automation. The processed materials included historical books classification, preparation of work tools for efficiency, and arrangement of library collections to optimize service qualityThe study concludes that student involvement positively impacts the sustainability of school library operations. It also emphasizes that students need to master library processing competencies before field practice. This strengthens the relationship between Library Science study programs and school libraries in improving the quality of library material processing.